Ground improvement - Kirsch, Klaus; Bell, A. L. (CRC Press, 2013)
This strongly practical and established guide to ground improvement, written by acknowledged experts, has been brought right up to date. It covers the major ground improvement techniques currently used worldwide and reflects recent improvements in productivity and control. An overview chapter sets the scene for the student or novice, and adds notes on blasting and ground freezing and on the emerging issue of the impact of improvement techniques on carbon emissions. The book remains strongly international in scope and with application across the field. It provides sound solutions to problems in.
Keywords: Soil stabilization.; Soil consolidation.; Grouting (Soil stabilization); elektronické knihy; electronic books